P1298SEASONAL VRIABILITIES OF HOME AND CLINIC BLOOD PRESSURE IN HEMODIALYSIS PATIENTS ARE DPEND ON VOLUME STATUS AND TEMPERATURE CHANGE IN MULTICENTER OF VARIOUS DISTRICTS IN JAPAN. (6th June 2020) - Ryuzaki, Munekazu; Komatsu, Motoaki; Soejima, Hidehisa; Soejima, Kazuaki; Ebihara, Itaru; Imai, Tsuyoshi; Yasunaga, Chikao; Suzuki, Yasushi; Hiramatsu, Makoto
Abstract: Background and Aims: In general population, there are weekly and seasonal variabilities of blood pressure (BP) which are supposed to be the risk of cardiovascular disease. Home BP is well correlated to the cardiovascular risk compared to clinic BP. We already reported home and clinic BP of hemodialysis (HD) patients fluctuate seasonally partly due to temperature. The aim of this study is to determine in large number of HD patients whether the seasonal BP variability correlates to the volume status and temperature. Method: One hundred sixty nine dialysis patients (93 male, 76 female) in ten Saiseikai hospitals in various districts in Japan were recruited. All patients were asked to measure BP at least four times a day in a sitting position, twice consecutively in the morning after urination before breakfast and medication and twice consecutively in the evening just before going to bed. The mean of twice measurements was defined as the data of measurement time. Data from Oct. 2015 to Oct. 2017 were analyzed. If the dialysis were performed 3 times a week (Mon, Wed, Fri), Monday was defined as 1st day. If the dialysis were performed on Tue. Thurs. and Sat., Tuesday was defined as 1st day. Seasonal variabilities in morning home BP and night home BP were evaluated. Seasonal changes in clinic BP just before and after HD were also evaluated in 61 patients. Results: Weekly home BP variability in the morning, 1st day 153±16 / 78±13 mmHg, 2nd day 144±28 / 76±12, 3rd day 150±14 / 77±13, 4th day 142±26 / 75±13, 5th day 149±14 / 77±12, 6th day 144±24 / 76±13, 7th day 149±16 / 78±13. Systolic home BPs in 1st, 3rd and 5th days were significantly elevated compared with 2nd, 4th and 6th days. Morning home BP significantly elevated gradually from 6th, 7th and to 1st day. Lowest SBP in the morning was 4th day but not 6th day which was the same as the previous result (CJASN 3: 416-422, 2008). Seasonal variability of morning home BP in 1st day was evident with the rise in autumn and winter (spring 153±19 / 78±12, summer 146±17 / 77±12, autumn 158±16* / 80±12, winter 156±19* / 80±13, * p<0.05 vs summer) (figure). There was almost same seasonal morning home BP variability in 4th day which had the lowest value of morning home BP in a week. Seasonal changes of night home BP in 5th day were not significant through four seasons, which night was supposed to be the driest volume status in a week. Seasonal changes in clinic BP just before and after HD, in 1st day before HD: spring 147±19 / 74±13 mmHg, summer 144±20 / 71±11, autumn 150±19 / 74±13, winter 147±21 / 74±12. Systolic BP in autumn was significantly elevated compared to summer. In the other clinic BPs before and after HD in 3rd and 5th days, there were no significant seasonal changes observed. Seasonal changes of highest temperature were significant (spring 19.9±3.1*°C, summer 30.9±2.6, autumn 23.3±2.7*, winter 8.5±2.8*, *p<0.05 vs summer). Morning BP of 1st day in a randomly selected patient was correlated with highest temperature (r=-0.397 p<0.0001). Discussion: There is seasonal home BP variability probably due to temperature change because BP was correlated well with temperature. Seasonal morning BP variability was evident in the 1st day of the HD week, but this seasonal home BP variability was disappeared measuring BP in the night without volume overload. We assumed that vasoconstriction due to change in temperature was enhanced by volume overload and sympathetic activation in the morning. Conclusion: In the large number of HD patients in multicenter of various districts in Japan, seasonal BP variabilities were affected by the volume status and temperature.